Role of Pharmacologic Paralysis in Acute Respiratory Distress Syndrome - Syed, Ammar; Kobzik, Alexander; Huang, David T. (Seminars in Respiratory and Critical Care Medicine, 2019)
The pharmacology and history of neuromuscular blockade in clinical care are complex, with multiple theoretical and observed potential benefits and potential harms. Past studies raised concern for long-term paresis, but more recent studies have not found evidence for harm, possibly due to changes in background care, neuromuscular blocking agent, and duration of blockade. Current use is highly variable, likely due to limited evidence for efficacy beyond short-term physiologic improvement and lingering concerns for harm. A recently completed large multicenter trial will provide further information on the role of pharmacologic paralysis in acute respiratory distress syndrome.
Keywords: neuromuscular blocking agents; pharmacologic paralysis; neuromuscular blockade; acute respiratory distress syndrome; clinical trial